Theoretical Investigation of Repurposed Drugs Potentially Capable of Binding to the Catalytic Site and the Secondary Binding Pocket of Subunit A of Ricin - França, Tanos C C; Botelho, Fernanda D; Drummond, Michael L; LaPlante, Steven R (ACS omega, 2022)
Recently, we reported a library of 82 compounds, selected from different databanks through virtual screening and docking studies, and pointed to 6 among them as potential repurposed dual binders to both the catalytic site and the secondary binding pockets of subunit A of ricin (RTA). Here, we report additional molecular modeling studies of an extended list of compounds from the original library. Rounds of flexible docking followed by molecular dynamics simulations and further rounds of MM-PBSA calculations using a more robust protocol, enabled a better investigation of the interactions of these compounds inside RTA, the elucidation of their dynamical behaviors, and updating the list of the most important residues for the ligand binding. Four compounds were pointed as potential repurposed ricin inhibitors that are worth being experimentally investigated.